Evaluation of endoscopic reintervention for self‐expandable metallic stent obstruction after stent‐in‐stent placement for malignant hilar biliary obstruction. (11th May 2019) - Okuno, Mitsuru; Mukai, Tsuyoshi; Iwashita, Takuji; Ichikawa, Hironao; Iwasa, Yuhei; Mita, Naoki; Yoshida, Kensaku; Iwata, Keisuke; Tomita, Eiichi; Shimizu, Masahito
Abstract: Background: Bilateral self‐expandable metallic stent (SEMS) placement is effective for long‐term management of unresectable malignant hilar biliary obstruction (UMHBO). However, endoscopic reintervention (ERI) for bilateral SEMSs is not well‐studied. This study aimed to evaluate ERI efficacy after stent‐in‐stent placement. Methods: Data of 31 patients who underwent ERI from May 2000 to July 2018 were analyzed. Results: The technical success rate was 80.7% (25/31) and no adverse events occurred. The functional success rate was 100% (25/25). In a multivariate logistic regression analysis, the angle between the bilateral SEMSs (ABBS) >104° (odds ratio 50.49, 95% CI 3.370–2131, P = 0.0039) and overgrowth (odds ratio 25.70, 95% CI 1.121–1234, P = 0.0423) were risk factors for ERI failure. Multiple liver metastases, which sometimes cause overgrowth, were also risk factors. After ERI, some patients underwent additional SEMS ( n = 4), plastic stent ( n = 14) placement, or internal cleaning of the initial SEMS alone ( n = 7). There were no significant intergroup differences in the 50% time to recurrent biliary obstruction. Conclusions: ABBS >104° and overgrowth were risk factors for ERI failure after stent‐in‐stent placement. In the decision‐making process for initial SEMS placement for UMHBO, patient condition should be considered, including the angle between bilateral bile ducts and multiple liver metastases. Abstract : Highlight Endoscopic reintervention for bilateral self‐expandable metallic stent placement is not well‐studied. Okuno and colleagues identified risk factors for endoscopic reintervention failure after stent‐in‐stent placement, and concluded that the angle between the bilateral bile ducts and the presence of multiple liver metastases must be considered when selecting the device for initial placement.